Gambaran Penyakit di Musim Panas dan Musim Dingin di Kota Makassar Periode 2023 - Sudirman, Farah Zhafirah; Makmun, Armanto (Yayasan Citra Cendekia Celebes, 2024)
Seasonal changes play a crucial role in public health dynamics in various parts of the world. The rainy season and summer each offer challenges that affect the physical, psychological and social well-being of individuals as well as the community at large. In tropical and subtropical regions, climate change and extreme weather are more pronounced, seasonal changes being a major factor in developing disease patterns. The aim of this research is to determine the description of disease in the summer and rainy season in Makassar City for the 2023 period. The variables used in this research are the summer and rainy season. The research method used was descriptive research using an observational approach to see the picture of disease in the summer and rainy season at RSP Ibnu Sina Makassar. The results of this study show that diseases in the rainy season from January to June 2023 are dyspepsia 442 cases (27.4%), typhoid fever 320 cases (19.8%), CAP 227 cases (14.1%), GEA 196 cases (12.2%), UTI 179 cases (11.1%), tonsillopharyngitis 134 cases (8.3%), pulmonary TB 51 cases (3.2%), bronchitis 25 cases (2%), diabetes mellitus 24 cases (1.9%). Based on the summer period from July to December 2023, namely dyspepsia 552 cases (36.58%), GEA totaling 341 cases (22.59%), CAP 263 cases (17.43%), typhoid fever 225 cases (14.91%), diabetes mellitus 78 cases (5.17 %), dengue hemorrhagic fever 50 cases (3.32%). The conclusion is that the most common diseases in the rainy season are dyspepsia and typhoid fever. Meanwhile, in summer there are dyspepsia, GEA, CAP, Typhoid fever, DM and DHF.